Education and Menstrual Hygiene: Practice and Awareness among Women in Ramechhap District - Ghising, Dipak (Journal of Health Promotion, 2025)
Menstrual hygiene is a fundamental right in women’s reproductive health influenced by several factors. This study examines the influence of education on menstrual hygiene and awareness among women in Ramechhap District. It specifically analyses the relationship between educational level and menstrual hygiene behaviors while taking into account control variables such as caste-ethnicity and religion. The study area comprised six wards in Khandadevi Rural Municipality, Ramechhap District, Nepal, and the sample comprised 351 female respondents. The secondary data were adopted from a 2025 baseline study report of the Community Development Society (CDS), Manthali, Ramechhap. The analysis employs binary logistic regression, which is fitted to the model at p<0.001. This analysis attributes 10 percent of the variance in the dependent variable to education, while also including control predictors such as caste-ethnicity and religion. The major findings reveal significant associations between education and several aspects of menstrual hygiene: access to adequate sanitation facilities, awareness of risks associated with poor menstrual hygiene, adequate information from Health Professionals, schools, or community programs, and comfort in discussing menstruation and menstrual hygiene. Higher levels of education increase menstrual hygiene awareness and practices, making individuals more aware than illiterate ones. Therefore, the study concludes that education exerts a more decisive influence on menstrual hygiene practices than other variables. It highlights the importance of policymakers and planners prioritizing women’s education in rural areas to improve menstrual hygiene practices and overall reproductive health.